Uma história urbana da vida cotidiana da autoconstrução do Jardim Nova Esperança em Goiânia (1979-1983) - Gomes, Lucius Fabius Ben Jah Jacob (2019)
The self-construction of Jardim Nova Esperança in Goiânia is still part of an urban history that is invisibilized and marginalized by the interpretation of the “legalized city”, “planned city” and/or “planned urbanismo” contained in the historiography of Goiânia. This work aims to construct, to visualize and to problematize the urban and daily history of this object, from 1979 to 1983. The general intention was articulated in interpreting, from the current of the urban spoliation how they were constructed the "problem of the dwelling" and its consequent absolute pauperization and urban spoliation arising from the urban phenomenon of self-construction of precarious housing in urban occupations in peripheral and dependent Brazilian capitalism. In association with this current of research, this construction was applied to the dialectical notions of daily life of José de Souza Martins and Henri Lefebvre in this present object, with the intention of constructing the dense dimension of the impasses and daily conquests of the historical events analyzed. We also sought to investigate in regional historiography on the subject, other cases of urban city occupations, and it was found that this urban phenomenon is not exclusive of our temporal cut, since it occurs in the city since the 1930s. pioneers, we aim to construct how the sociability of the creation of the periodic community media by the residents, their production, social function and linkage with the political daily life of the occupation occurred. With this investigation it was possible to work with community newspapers: Comunicados, Boletins e Jornal 4 de Outubro. It was also objective, to construct and to intend the possible housing policies of the Municipality of Goiânia in relation to the housing policy self-constructed by the residents. It was verified from this point, that the housing policies created by the residents became effective in the daily life of the occupation. In addition, it was aimed to analyze the assumptions, strategies, intentions and discursive constructions of two newspapers of local Goianian media. That is, to investigate what were the interpretations of the reports of the newspapers O Popular and Opção on the studied urban occupation. It was verified that these two newspapers constructed discourses that aimed to dismiss the historical sense of this occupation, constructing pejorative versions, hermetic and above all distanced from the daily urban history experienced in this urban occupation.